A review of finite element modeling and surgical simulation of meniscal tear in knee joint: progress and challenges - Yu, Chengyue; Duan, Xiaoyuan; Gou, Yu; Liu, Kexin; Zhao, Wenjun; Gao, Xiaokang; Wang, Lupeng; Liu, Jinwei; Xu, Jiahe; Zeng, Jiashi; Chen, Desheng; Xing, Guosheng; et al. (Frontiers in Medicine, 2025)
As one of the essential tissues of the knee joint, the meniscus plays a crucial role in load transmission, shock absorption and joint stability. Meniscal tears caused by degenerative diseases and traumatic injuries are prevalent. Meniscal repair or meniscectomy is considered the first choice for treatment. Because the knee joint cannot be conducted in vivo, and the reproducibility of in vitro experiments is poor, finite element analysis has become an important tool for evaluating clinical surgical techniques. This review summarizes the latest research progress on meniscal tears and corresponding surgical techniques from the perspective of numerical calculation and clinical analysis for the first time. The study found that establishing an accurate finite element model requires consideration of multiple factors and rigorous clinical validation. The purpose of this review is to provide researchers with more reasonable finite element models, evaluate the biomechanical characteristics of meniscal tears and related surgical techniques, and provide more systematic research for clinical practice to improve surgical techniques further. This presents new research opportunities for the precise diagnosis and treatment of knee joint diseases.